Sociology : study of the social sphere - Atal, Yogesh (Always learning., 2015)
As in all growing disciplines, sociology has witnessed continuous advances in our knowledge about the phenomena it studies. Over time, some themes are ped, and new concerns are incorporated, necessitating a reprioritization of themes to meet changing times, even as older and classical texts become less relevant. Sociology: Study of the Social Sphere is a detailed and concise attempt to fulfill the need for new texts that reflect this. This textbook will provide readers with a solid foundation on which to build expertise in specialized branches of the discipline. It will serve as an introduction to the discipline for students and teachers of sociology, as well as for those taking courses on management, public administration, anthropology and social work.